ANALYSIS OF ANTI COMPUTER FORENSICS TECHNIQUE USING OVERWRITING METADATA METHOD ON DIGITAL EVIDENCE - Julian Saputra; Jusia Amanda Ginting (Universitas Bunda Mulia, 2022)
The development of technology during this globalization period is very fast and rapid, especially during the pandemic in this world which makes all activities like education, work etc. carried out online-based. Because, with the increase in the use of online-based media, a problem arises like crimes that use online or digital media as an intermediary known as cybercrime. With this cybercrime, a science that can be used in securing personal data is needed, namely anti-computer forensic science. This research is focused on the analysis and implementation of forensic anti-computer science in securing personal files. In this study, the anti-computer forensic method that will be analyzed and applied is metadata overwriting, data destruction, and data hiding.In this test, the three methods will be broken down again into several sub methods or techniques such as file obscure manipulation, file timestamp manipulation, secure deletion, and data encryption. The results of the application of several categories of techniques will be written and then analyzed.The results of the study showed that the technique tested was very good and safe in securing personal files so that they could not be detected by systems or digital forensic software but there were still weaknesses, namely in the data hiding section if the password or key used was simple, it would be easy to hack.